Effectiveness of intradialytic muscle stretching exercise onmuscle cramps among patients undergoing maintenance hemodialysis in Oman - A randomized controlled trial - Iman Al Rahbi; Eilean Rathinasamy Lazarus; Omar AlZaabi; Huda Al-Noumani (Journal of Health Sciences, 2025)
Introduction: Patients with end-stage renal disease (ESRD) typically exhibit symptoms of the “uremic” syndrome and lower quality of life. Intradialytic muscle stretching exercise has been proposed as a method to improve activity levels by reducing uremic symptoms. In Oman, hypertension and diabetes increase the risk of ESRD, the sixth leading cause of death. ESRD patients in Oman require more dialysis, straining healthcare financial burden.